KCPR San Luis Obispo: Domestic Dispute Legal [station] ID, 30 seconds - Boelter, Trevor::::::broadcaster:::; James Cushing::::::actor:::; Melissa Underwood::::::actor:::
Station identification recording, with an intro spoken by Trevor Boelter, and James Cushing and Melissa Underwood acting as the arguing couple.